ANALYSIS OF MATHEMATICAL CREATIVE THINKING BASED ON THE SELF-CONFIDENCE OF JUNIOR HIGH SCHOOL STUDENTS - Dalila Sabrina; Annisa Swastika; Minsih Minsih (JME (Journal of Mathematics Education), 2024)
Creative thinking skills were important for students to have to solve math problems appropriately. This article aims to provide an overview of junior high school students' ability to think creatively. The images to be studied are related to students' abilities for fluency, flexibility, and originality . The topic in this article is the seventh-grade students of SMP Muhammadiyah Kottabarat Surakarta Special Program, with a total of 16 students who will be categorized based on high, medium, and low self- confidence . The data collection technique used a test in the form of five description questions in the material of rectangular flat building problems and interviews. The method used is the descriptive approach. The data analysis techniques in this article are based on Miles and Huberman, namely data collection, data reduction, data presentation and verification. The results show that students' creative thinking skills are divided into 3 categories: 6% in the high category, 75% in the medium category, and 19% in the low category. This result shows that students' ability to think creatively in solving rectangular flat problems is relatively easy, which means that their capacity to solve rectangular flat problems based on creative thinking steps hasn't been maximized .